Des-reterritorialização: percursos possíveisdo romance afro-brasileiro recente - Paulo C. Thomaz (Estudos de Literatura Brasileira Contemporânea)
This study analyzes, through the concept of multiterritoriality, by geographerRoger Haesbaert, the diasporic journeys of the characters ofUm defeito de cor(2006), an African-Brazilian novel written by Ana Maria Gonçalves. Consideringthe novel, which takes place in Africa and Brazil in the nineteenth-century, wewill focus on the protagonist, Kehinde, in her material and symbolic mobilityaround African and American continents. To Haesbaert, the immanent aspect ofmultiterritoriality in individual lives and in different human groups has beendepreciated by the “myth” of deterritorialization. Instead of a simplisticuprooting dispossession, there would be a permanent process of, a spatiallydiscontinuous and highly complex repossession. Thus, it is through the action ofmoving as, on one hand, symbolic and cultural, and, on the other, political andeconomic dereterritorialzation that these diasporic journeys of the characters ofthe novel are thought.